2003
DOI: 10.1111/j.1349-7006.2003.tb01408.x
|View full text |Cite
|
Sign up to set email alerts
|

Extragonadal germ cell tumors in Japan

Abstract: Extragonadal germ cell tumors (EGCT) represent only 2-5% of adult germ cell malignancies. Some publications from Asia have reported inferior treatment outcomes compared to data from an international study group. To ascertain whether this is generally the case, here we analyze treatment outcomes for 30 Japanese patients with EGCT. The medical records of 30 patients (25 nonseminomas and 4 pure seminomas) treated from 1992 to 2002 were reviewed retrospectively. All patients with seminoma achieved long survival ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…The other reasons for suboptimal treatment were poor patient compliance, the concomitant presence of other medical conditions and delayed diagnosis/therapy. Recent studies have also reported suboptimal treatment of a significant number of patients in a similar way to the present study [14,15,16,17]. However, these studies did not assess the quality of the chemotherapeutic management in detail.…”
Section: Discussionsupporting
confidence: 65%
“…The other reasons for suboptimal treatment were poor patient compliance, the concomitant presence of other medical conditions and delayed diagnosis/therapy. Recent studies have also reported suboptimal treatment of a significant number of patients in a similar way to the present study [14,15,16,17]. However, these studies did not assess the quality of the chemotherapeutic management in detail.…”
Section: Discussionsupporting
confidence: 65%
“…In the largest international multicenter analysis conducted to date, all 635 patients with malignant EGCT were male 3 . Smaller national or institutional studies from Canada, Japan, Taiwan, Turkey, and India have found that 3 of 40, 8 1 of 30, 9 5 of 59, 4 1 of 18, 10 and 11 of 37 11 patients, respectively, were female, with most having intracranial germinomas or nonseminomatous GCT in the mediastinum or retroperitoneum. Studies in Belgium and Korea included 4 and 41 female patients, respectively, who had nonseminomatous GCT or mature teratomas of the retroperitoneum or other sites 12,13…”
Section: Discussionmentioning
confidence: 99%
“…Germ cell tumours (GCTs) most frequently arise in the gonads, but some develop extragonadally (Schmoll, 2002) (Ebi et al. , 2003) (Bokemeyer et al.…”
Section: Introductionmentioning
confidence: 99%
“…Germ cell tumours (GCTs) most frequently arise in the gonads, but some develop extragonadally (Schmoll, 2002) (Ebi et al, 2003) (Bokemeyer et al, 2002) (Bokemeyer et al, 2003). Extragonadal germ cell tumours (EGCTs) have similar morphology as gonadal germ cell tumours (GGCT), and most often occur in the midline of the body, e.g.…”
Section: Introductionmentioning
confidence: 99%